FINANCIAL PERFORMANCE ANALYSIS OF STOCK PRICES WITH DIVIDEND POLICY AS INTERVENING VARIABLES IN THE METAL MINING SECTOR - Mia Maharani; Zulkifli Zulkifli; Widarto Rachbini (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine, test, and analyze the effect of the current ratio, cash ratio, debt to asset ratio, debt to equity ratio, return on assets, and return on equity on stock prices with dividend policy as an intervening variable. The case study in this study is a metal mining sector company listed on the Indonesia Stock Exchange (IDX) for the period 2015 – 2020. This study is quantitative with data analysis techniques used as descriptive analysis using financial ratio analysis. Collection by collecting financial reports on the website www.IDX.co.id in 2015-2020. The population in this study consisted of 11 sub-sector companies. The research sample was five companies, and the sampling technique used purposive sampling. The data analysis method used in this research is using SmartPLS version 3.0. The results show that the current and cash ratios are unrelated to dividend policy. Debt to asset and debt to equity ratios are unrelated to dividend policy. Return on assets and return on equity are also not significant to dividend policy. The current ratio and cash ratio have a significant effect on stock prices. Debt to asset ratio and debt to equity ratio significantly affect stock prices. Return on assets and return on equity have a significant effect on dividend policy. And dividend policy has a significant effect on stock prices, so that dividend policy can be an intervening variable on stock prices in metal mining sector companies listed on the Indonesian Stock Exchange (IDX) for the 2015-2020 period.